(untitled) (Research, Society and Development, 2020)
In order to increase the quality of information management, the Ministry of Health launched the Basic Care Health Information System (SISAB), which is implemented through the e-SUS Basic Care strategy (e-SUS-AB), through Ordinance 1412 of July 13, 2013. The objective of this article was to evaluate the e-SUS - AB service from the perspective of the Municipal Health Managers of the Pianco Valley, how it has facilitated the development of activities and decision-making of Municipal Health Managers through the reports generated by the System. The methodology used was the Grounded Theory (GT), a qualitative method of elaborating a theory based on empirical data from a social reality. Faced with the analysis, it was possible to understand how the regional health managers use the e-SUS - AB reports and how the information produced influence the decision-making process. It was possible to evaluate that the strategy is indispensable for management activities, but some factors still compromise the work.